Estudio explora las estrategias corporativas de empresas multinegocios en Colombia (2021)
An investigation led by two professors from the EAFIT School of Administration describes the way in which multi-business companies in the country design and adapt their corporate strategies from top management. The most important finding has to do with when companies become multi-businesses and top management must define corporate strategy: how it will reconfigure its portfolios (invest and divest) and how it will jointly manage those businesses.